Moses Quellwasserwunder Ex 17 und Paraschat Chukkat (Num 20) in jüdischen und christlichen Bildrezeptionen - Rotach, Brigitta (De Gruyter, 2023)
The miracle of Moses striking water from a rock in the desert is told twice in the Torah / Old Testament. The different Jewish and Christian receptions of this account are fascinating, expressing how these texts were understood, the zeitgeist, and the dominant questions in the respective societies. They either emphasize Moses' sin or the radiant prefiguration of the Messiah - either death in the desert or life-saving water
Description based on online resource; title from PDF title page (publisher's Web site, viewed 09. Dez 2023)
Keywords: Mose -- Biblische Person; Bibel -- Numeri -- 20; Bibel -- Exodus -- 17; Bibel -- Numeri -- 20,1-13; Bibel -- Exodus -- 17,1-7; Hebräische Bibel; Interreligiöser Dialog; Kunstempfang; Moses; RELIGION / Biblical Criticism & Interpretation / Old Testament; Theologie; Wunder; Judentum; Rezeption; Christentum; Kunst